2011
DOI: 10.1080/00015458.2011.11680711
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients with Ruptured Abdominal Aortic Aneurysm after Cardiopulmonary Resuscitation

Abstract: Requirement of CPR has a detrimental effect on RAAA-patient outcome. Patients receiving CPR prior to surgery have no survival chance. We advocate that surgery in these patients should not be undertaken. Hardman Index has a predictive value concerning 30-day mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…After systematic database searches and removal of duplicate records, 7210 citations were screened (Fig) . Sixty-two publications were eligible for review, of which 16 reported management and outcomes for patients with preoperative cardiac arrest (Table II). 3,[5][6][7][8][9][10][11][12][13][14]18,[23][24][25] Thirteen articles were single institution series, whereas three were multi-center or database studies. All were retrospective, Oxford level of evidence IV studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After systematic database searches and removal of duplicate records, 7210 citations were screened (Fig) . Sixty-two publications were eligible for review, of which 16 reported management and outcomes for patients with preoperative cardiac arrest (Table II). 3,[5][6][7][8][9][10][11][12][13][14]18,[23][24][25] Thirteen articles were single institution series, whereas three were multi-center or database studies. All were retrospective, Oxford level of evidence IV studies.…”
Section: Resultsmentioning
confidence: 99%
“…19 Two studies concluded that aortic intervention should not be performed in patients with preoperative cardiac arrest. 8,14 In both studies, which included 290 patients with rAAA and 22 patients with cardiac arrest, mortality after cardiac arrest was 100%. In contrast, five studies endorse attempting repair in this population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies that reported a 100% mortality rate in preoperatively resuscitated patients advocate that invasive treatment should be denied. 7,9 In contrast, 67% and 72.8% 30-day mortality rates have been observed in patients with an RAAA that required CPR. 6,10 To our knowledge, this is the first multicenter study to describe survivors after resuscitation before RAAA surgery.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, a slim body of low-level literature are adamant that these patients are unlikely to survive. [7][8][9] Senior authors of the present study have experienced that some patients might survive after the unfortunate combination of CPR before RAAA treatment.…”
mentioning
confidence: 82%